Cervical cancer stem cells. (December 2015) - Yao, Tingting; Lu, Rongbiao; Zhang, Yizhen; Zhang, Ya; Zhao, Chenyang; Lin, Rongchun; Lin, Zhongqiu
Abstract: The concept of cancer stem cells (CSC) has been established over the past decade or so, and their role in carcinogenic processes has been confirmed. In this review, we focus on cervical CSCs, including (1) their purported origin, (2) markers used for cervical CSC identification, (3) alterations to signalling pathways in cervical cancer and (4) the cancer stem cell niche. Although cervical CSCs have not yet been definitively identified and characterized, future studies pursuing them as therapeutic targets may provide novel insights for treatment of cervical cancer.